Pengaruh Personal Selling dan Public Relation Terhadap Keputusan Nasabah Memilih Tabungan Easy Wadī‘ah pada BSI KCP Sumenep Trunojoyo - Hidayati, Nurul; Zulfa, Kamalina (Al Maal: Journal of Islamic Economics and Banking, 2024)
This study aims to determine the effect of personal selling and public relations on customers' decisions to choose easy wadi'ah savings. This research method is quantitative research with the type of associative research. This research uses non-probability sampling with purposive sampling technique as many as 275 respondents. Based on the results of the research that has been done, it can be concluded that partially personal selling (X1) and public relations (X2) have a positive and significant effect on the customer's decision to choose easy wadi'ah savings. Simultaneously personal selling and public relations have a positive and significant effect on the customer's decision to choose easy wadi'ah savings. The influence of personal selling and public relations variables on the customer's decision to choose easy wadi'ah savings is 0.334, which means that the personal selling and public relations variables can explain 33.4% of the customer's decision variables. While the remaining 66.6% is explained by other variables that were not examined in this study.